ANALYSIS OF THE CONSEQUENCES OF EARTHQUAKES IN TURKEY 06.02.2023 USING RADAR INTERFEROMETRY - ZATSERKOVNY, Vitalii; TSIUPA, Irina; OSTAPENKO, Hryhorii; DE DONATIS, Mauro; ILYIN, Leonid (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. The article studies the consequences of a series of earthquakes that occurred on February 6, 2023 in Turkey, which caused large-scale destruction and tens of thousands of victims, and became the deadliest in the world in the last 10 years. Research on the effects of earthquakes is important and can be used in emergency management and disaster recovery, to improve building standards, develop earthquake-resistant infrastructure, etc. Methods. The study was performed using modern methods of remote sensing and geographic information systems. To quantify the surface displacement, we used the method of synthetic aperture interferometry (InSAR) based on Sentinel-1 satellite images in the SNAP application. To improve the accuracy of the results, the Goldstein filter was applied and the phase unwrapping was performed using the external Snaphu software module. To compensate for data distortion, terrain correction was performed using the Doppler terrain correction operator to make the geometric image as close to the real world as possible. Results. The interferograms obtained before and after the earthquakes were analyzed. The results indicate significant surface deformations, especially in the area of the East Anatolian fault, with a maximum subsidence of 110 cm and more pronounced fault lines. The interferograms show that the earthquakes have caused significant changes in the fault structure, which may affect further seismic activity in the region. Diagrams and maps showing the impact of earthquakes on the surface and crust in the southeastern part of Turkey were constructed. Сonclusions. This study demonstrates the possibility of using InSAR technology to monitor the deformation of the earth’s surface caused by recent earthquakes. The data obtained can be used to assess damage, identify risk areas, and develop measures to reduce seismic hazards.